A Cu–Pd–V System Filler Alloy for Silicon Nitride Ceramic Joining and the Interfacial Reactions. Issue 8 (28th June 2014) - Xiong, Hua‐Ping; Chen, Bo; Pan, Yu; Zhao, Hai‐Sheng; Mao, Wei; Cheng, Yao‐Yong
<x xml:space="preserve">Abstract</x> A Cu–Pd–V brazing alloy with the composition of Cu–(38.0 42.0)Pd–(7.0 10.0)V (in wt.%) was designed as a filler for joining Si3N4. Its wettability on Si3N4 ceramic was measured with the sessile drop method. It was shown that the Cu–Pd–V alloy gave a contact angle of 71° at 1473 K. The filler alloy was fabricated into foils with a thickness of 0.15 mm. The Si3N4–Si3N4 joints brazed at 1443 K for 10 min exhibit average three‐point bend strength of 263 MPa at room temperature, and the joint strengths at 973 K and 1073 K are 277 MPa and 218 MPa, respectively. The analysis results of SEM, XRD, and TEM for the brazed joint indicate the presence of V2N at the surface of the Si3N4. The increase of the thickness of V2N reaction layer obeyed parabolic law, and the parabolic rate constant (k) can be described as k = 2.8739 × 10−9 exp(−162989.4/RT) m2/s. Pd2Si and Cu3Pd compounds as well as (Cu, Pd) solid solution were detected in the central part of the joints. The presence of (Cu, Pd) phases and especially refractory Pd2Si compounds within the joints should contribute to the stable high‐temperature property. The interfacial reaction mechanisms were discussed.